Population parameters of the fish fauna in a long‐established Amazonian reservoir (Amapá, Brazil). (16th December 2014) - Sá‐Oliveira, J. C.; Angelini, R.; Isaac‐Nahum, V. J.
Summary The present study focused on the fish fauna of the 44‐year‐old Coaracy Nunes reservoir in the northern Amazon basin, producing estimates of the growth constant (k), maximum and asymptotic body lengths and weights, natural mortality (M), the consumption/biomass ratio (QB) (intake of food by a group over a year), the Aspect ratio (Ar) of the caudal fin, growth performance (Φ), longevity, and trophic level for 45 fish species. Species collection was divided into eight sampling campaigns between May 2009 and July 2010. Gillnets were used in four of the sampling sites. The results revealed that (i) the most predominant species are Ageneiosus ucayalensis, Hemiodus unimaculatus, Serrasalmus gibbus and Geophagus proximus; (ii) small and medium‐sized fishes predominated in the community, characterized by high rates of growth and natural mortality, consistent with a predominance of r‐strategists; (iii) the body lengths of the detritivore species were similar to those of the piscivores, which are normally larger, but with higher growth rates, more similar to those recorded for the omnivores; (iv) consumption/biomass ratio (QB) × body length relationship is higher in the detritivores than in the omnivores and piscivores (which were similar to each other). Overall, the reservoir habitat appears to be advantageous to detritivorous fish species.